Deterritorialising climate: ocean-based approaches to adaptation governance (2020)

(untitled)
This research asks how the Pacific climate system of El Niño Southern Oscillation (ENSO) is conceived and represented in the boundary-making practices of three knowledge communities: a) ocean science (i.e. Pacific marine biogeographies), b) environmental governance (i.e. Pacific adaptation frameworks), and c) local and traditional environmental knowledge (i.e. coastal subsistence communities in Timor-Leste). Ultimately, the project asks whether these disciplinary delineations of ENSO-related climate events promote effective adaptation governance.